PENGUATAN KADER POSYANDU TERHADAP PELAYANAN KIA PADA MASA PANDEMI COVID-19 - Ismaulidia Nurvembrianti; Novi Arianti; Indry Harvika; Mega Oktaviana (Politeknik 'Aisyiyah Pontianak, 2022)
The COVID-19 pandemic has affected maternal and child health services, resulting in a decrease in the target coverage of maternal and child health services. The implementation of local area monitoring of maternal and child health (PWS) with maternal and child health indicators (KIA) is one indicator of reducing maternal and infant mortality rates. The government is responsible for providing Maternal and Child health services (KIA), especially for infants and toddlers, to optimize the health service users of posyandu cadres, it is necessary to deliver information to the public. The purpose of this service is to increase the knowledge of posyandu cadres on infant health services during the Covid-19 pandemic. Methods The implementation of the service uses the lecturing and discussion method in the form of counseling to posyandu cadres, the media used is a google meet video teleconference. The participants of this activity were posyandu cadres in the UPTD Puskesmas Pontianak Barat. The results showed that counseling could increase postyandu cadres' knowledge related to infant services that needed to be carried out during the covid-19 pandemic.